2005
DOI: 10.1249/01.mss.0000170128.78432.96
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheology, Sickle Cell Trait, and α-Thalassemia in Athletes: Effects of Exercise

Abstract: These results demonstrate that HbAS group is prone to higher RBC rigidity, which might lead to hemorheological alterations that are thought to participate to microcirculation disorders. However, these alterations are limited by the coexistence of alpha-thalassemia. Moreover, hemorheological parameters were not further impaired in SCT athletes with or without alpha-thalassemia in response to exercise. Training status might be protective from physiological stresses usually leading to sickling process in SCT carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
58
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 25 publications
12
58
3
1
Order By: Relevance
“…Patients with α thalassemia and on hydroxyurea therapy were excluded from the present study since they are known to have abnormal RBC rheology. [9][10][11][12] All subjects provided informed consent and the ethics committee of the Academic Hospitals of Pointe-à-Pitre approved the study.…”
Section: Subjects and Blood Samplingmentioning
confidence: 99%
“…Patients with α thalassemia and on hydroxyurea therapy were excluded from the present study since they are known to have abnormal RBC rheology. [9][10][11][12] All subjects provided informed consent and the ethics committee of the Academic Hospitals of Pointe-à-Pitre approved the study.…”
Section: Subjects and Blood Samplingmentioning
confidence: 99%
“…Blood flow is also deeply affected by blood apparent viscosity (Poiseuille's law). Several studies have thus far shown the presence of lower RBC deformability and higher blood apparent viscosity among SCT carriers compared with HbAA control (C) subjects (9,18,19,47). Furthermore, the lower RBC deformability of SCT carriers could lead to endothelial damage, activation of endothelial cells, and thus promote endothelial cell-blood cell interactions, leading to inflammation.…”
mentioning
confidence: 99%
“…A test of solubility confirmed the presence of Hb S. Positive test results for SCT were determined by the presence of Hb S (Ͻ50%) and a normal percentage of Hb A2 (16). Hb concentration, hematocrit (Hct), percentage of reticulocytes, and mean corpuscular volume were also studied for the indirect diagnosis of anemia and ␣-thalassaemia, which results in hematological modifications (20,26).…”
Section: Sct Diagnosis and Blood Analysismentioning
confidence: 99%
“…The physical and physiological behavior of exercising SCT carriers (AS) remains equivocal, and controversial data have been documented. Although the presence of Hb S should result in lower aerobic capacity, most studies have reported similar aerobic performances in AS and controls (1,13,20,24). Impaired O 2 delivery to muscles from AS RBCs during exercise could result in a greater participation of anaerobic metabolism in exercising muscles.…”
mentioning
confidence: 99%